Towards symmetry : examining marital arrangements in contemporary Singapore - Koo, Wan Ning (2015)
Singapore is a society flanked by tradition and modernity, Asian perspective of the family, and Western ideas of individualism. Each of these factors suggest a different trajectory in marriages. Thus, in this transitory position, how do Singaporeans make sense of gender relations within their marriage? Drawing on in-depth interviews with young married couples and their parents, this study seeks to examine how do people brought up in families where gender division of labour and power dynamics are more clearly and stereotypically articulated, form their own marriages in a period when those gendered assumptions are gradually falling apart? What informs them of the way they want their marriage to be, and what is the process by which they come to these arrangements? By answering these questions, this study will also shed light on whether marriage has moved towards greater equality between husbands and wives. Through my findings, I showed that this movement towards greater conjugal symmetry is resultant of the way individuals negotiate their marriage based upon their attitudes with the intricacies of marriage, parental influence, and institutional policies surrounding the family.